2002
DOI: 10.1002/art.10384
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytokine production and proliferation of T cells from patients with anti‐proteinase 3‐ and antimyeloperoxidase‐associated vasculitis, in response to proteinase 3 and myeloperoxidase

Abstract: Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 41 publications
4
69
0
1
Order By: Relevance
“…The notion that tryptophan degradation was due to monocyte/macrophage up-regulation of IDO through the action of proinflammatory cytokines was supported by the presence of elevated levels of serum neopterin in patients with acute disease and patients with disease in remission. Neopterin is a low molecular mass product of monocyte/macrophages, the up-regulation of which is similarly influenced by proinflammatory cytokines such as IFN␥ (13 [8][9][10][11][12][13][14][15][16][17][18][19][20] in healthy controls; P Ͻ 0.001 for patients with acute disease versus controls and P Ͻ 0.05 for patients with disease in remission versus controls, by one-way ANOVA) ( Figure 4C). Serum neopterin levels remained elevated in patients compared with controls when corrected for renal function.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion that tryptophan degradation was due to monocyte/macrophage up-regulation of IDO through the action of proinflammatory cytokines was supported by the presence of elevated levels of serum neopterin in patients with acute disease and patients with disease in remission. Neopterin is a low molecular mass product of monocyte/macrophages, the up-regulation of which is similarly influenced by proinflammatory cytokines such as IFN␥ (13 [8][9][10][11][12][13][14][15][16][17][18][19][20] in healthy controls; P Ͻ 0.001 for patients with acute disease versus controls and P Ͻ 0.05 for patients with disease in remission versus controls, by one-way ANOVA) ( Figure 4C). Serum neopterin levels remained elevated in patients compared with controls when corrected for renal function.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Our group and others have shown that T cells responding to the autoantigens MPO and proteinase 3 (PR3) are found in patients with active disease (9)(10)(11), and persistent T cell activation has also been reported (12). Additionally, ANCA are class-switched antibodies, which therefore require T cell help for their generation.…”
mentioning
confidence: 96%
“…However, these observations are not uniform, and predominance of CD3 ϩ cells, eosinophils, and Th2 cytokines has been reported in a study of nasal biopsies from patients with Wegner's granulomatosis (81). The presence of T cells that respond to the likely target antigens, MPO and PR3, in patients with ANCA-associated GN provides evidence for the involvement of T cell-directed autoimmunity (82)(83)(84)(85)(86). The immunodominant epitopes have not been defined precisely, but for PR3, predominant T cell-reactive residues in three peptide regions involving the C terminal of the propeptide and the signal sequence have been identified (87).…”
Section: T Cells In Anca-associated Crescentic Gnmentioning
confidence: 99%
“…IFN-␥ and IL-4 concentrations were determined with the PeliKine Compact IFN-␥-and IL-4 enzyme-linked immunosorbent assay (ELISA) kits in accordance with the guidelines provided by the supplier (Central Laboratory of the Blood Transfusion Service, Amsterdam, The Netherlands). IL-10 concentrations were determined as described previously (14). Optical densities at 450 to 575 nm were measured with SOFTMAX software.…”
Section: Patients and Controls (I) Bud Patientsmentioning
confidence: 99%